Analisis Hubungan Responveness, Responsibility dan Accountability Terhadap Tingkat Kepuasan Masyarakat - Utami , Iis Torisa (Jayapangus Press, 2023)
In the era of the Covid-19 pandemic, service activities to the community were limited by government regulations, which affected employee performance in fulfilling the wishes of the community in document processing. This study aims to explain the relationship between the variables of responsiveness, responsibility, and accountability for community satisfaction during the Covid-19 pandemic. The descriptive quantitative research method, with data analysis used, is Pearson correlation and distribution of questionnaires to 20 respondents who came to the Babakan urban village office in Tangerang City. The results of the study showed that the correlation value of the responsiveness variable to community satisfaction was 0.181 with a significance of 0.446 > 0.05, it was stated that the responsiveness variable did not exist a relationship between responsiveness with the level of community satisfaction. While the Pearson correlation variable of responsibility for community satisfaction is 0.586 with a significance of 0.015 ≤ 0.05 has a significant relationship between the variable of responsibility and community satisfaction, and the variable of accountability for community satisfaction of 0.575 with a significant 0.008 ≤ sig. 0.05 has a significant relationship between accountability variables and community satisfaction. So the implementation of services for the community in any condition still pays attention to the policies or rules of public service administration that prioritize the values and norms that apply in the community.